2016
DOI: 10.3390/catal6120208
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Evolution Reaction of γ-Mo0.5W0.5 C Achieved by High Pressure High Temperature Synthesis

Abstract: For the first time, the hydrogen evolution reaction (HER) electrocatalytic performances of incompressible γ-Mo 0.5 W 0.5 C, prepared by high-pressure, high-temperature (HPHT) synthesis, were investigated in the electrolyte. The polarization curve of the γ-Mo 0.5 W 0.5 C cathode exhibits the current density of 50 mA·cm −2 at an overpotential value of 320 mV. The corresponding Tafel slope of the incompressible γ-Mo 0.5 W 0.5 C is 74 mV·dec −1 . After a 1000-cycle test, and then exposure to the air for six months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…S1 †), while the peaks marked with triangles derive from the Cu substrate. 24,25 It has been reported that Mo 2 C has high stability in inert gas or reduction gas. In our case, XRD measurements have been conducted to probe the stability as a function of temperature ( Fig.…”
mentioning
confidence: 99%
“…S1 †), while the peaks marked with triangles derive from the Cu substrate. 24,25 It has been reported that Mo 2 C has high stability in inert gas or reduction gas. In our case, XRD measurements have been conducted to probe the stability as a function of temperature ( Fig.…”
mentioning
confidence: 99%